Regulation of adiponectin and leptin secretion and expression by insulin through a PI3K-PDE3B dependent mechanism in rat primary adipocytes - Cong, Li (Portland Press Ltd., 2007)
Adiponectin is intimately involved in the regulation of insulin sensitivity, carbohydrate and lipid metabolism, and cardiovascular functions. The circulating concentration of adiponectin is decreased in obesity and Type 2 diabetes. The present study attempts to elucidate the mechanisms underlying the regulation of adiponectin secretion and expression in rat primary adipocytes. The β-agonist, isoprenaline, decreased adiponectin secretion and expression in a dose-dependent manner in primary adipocytes. Importantly, such an inhibitory effect could be blocked by insulin. The opposing effects of isoprenaline and insulin could be explained by differential regulation of intracellular cAMP levels, since cAMP analogues suppressed adiponectin secretion and expression in a fashion similar to isoprenaline, and insulin blocked the inhibitory effects of the cAMP analogue hydrolysable by PDE (phosphodiesterase). A specific PDE3 inhibitor, milrinone, and PI3K (phosphoinositide 3-kinase) inhibitors abolished the effects of insulin on adiponectin secretion and expression. In the same studies, leptin secretion and expression displayed a similar pattern of regulation to adiponectin. We conclude that insulin and β-agonists act directly at the adipocytes in opposing fashions to regulate the production of adiponectin and leptin, and that a PI3K-PDE3B-cAMP pathway mediates the effects of insulin to restore β-agonist/cAMP-suppressed secretion and expression of these two adipokines.